2014
DOI: 10.1155/2014/681853
|View full text |Cite
|
Sign up to set email alerts
|

Articulated Arm Coordinate Measuring Machine Calibration by Laser Tracker Multilateration

Abstract: A new procedure for the calibration of an articulated arm coordinate measuring machine (AACMM) is presented in this paper. First, a self-calibration algorithm of four laser trackers (LTs) is developed. The spatial localization of a retroreflector target, placed in different positions within the workspace, is determined by means of a geometric multilateration system constructed from the four LTs. Next, a nonlinear optimization algorithm for the identification procedure of the AACMM is explained. An objective fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…The multilateration method was initially proposed for high-accuracy surface form metrology [81]. Recently, it is widely used for calibrating CMMs and machine tools [183]. A laser-based multilateration system is typically composed of three laser-based measuring stations and a wide-angle retroreflecting target.…”
Section: Multilateration Systemsmentioning
confidence: 99%
“…The multilateration method was initially proposed for high-accuracy surface form metrology [81]. Recently, it is widely used for calibrating CMMs and machine tools [183]. A laser-based multilateration system is typically composed of three laser-based measuring stations and a wide-angle retroreflecting target.…”
Section: Multilateration Systemsmentioning
confidence: 99%
“…Furthermore, it is proved with these tests that the real accuracy of the laser tracker obtained in the experimental procedure, ±0.005 mm, is better than the one specified by the manufacturer in the product specification for the model Leica LTD600D, ±10 lm ± 0.5 lm/m, corresponding to an accuracy of ±10.6 lm for a 1.2 m length. A proposal for fixing the lack of accuracy of laser trackers that is required for AACMM's calibration is the use of multiple laser trackers through multilateration [34,10]. This technique enables a decrease in the measurement uncertainty by means of angular noise reduction.…”
Section: Evaluation Test On a Linear Guidementioning
confidence: 99%
“…Kovac and Frank [6] developed a new high precision measuring device for AACMM testing and calibration based on laser interferometer measurements along a line gauge beam. Santolaria et al [5,[7][8][9][10] reported a method to calibrate an AACMM based on the Denavit-Hartenberg kinematic model parameters [11]. These parameters are optimized measuring a calibrated ball bar gauge located at different orientations and positions of the AACMM working volume.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its flexibility and portability, there is a growing demand for applications at industrial sites [3]. However, as a multi-joint serial structure like robotic arm [4,5] AACMMs have lower accuracy comparing with the normal coordinate measuring machines.…”
Section: Introductionmentioning
confidence: 99%